Multiscreen consumption and polarization on Twitter during debates in Spain (2023) - Zamora-Martínez, Patricia; Berrocal-Gonzalo, Salomé; González-Neira, Ana (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Currently, the viewership of electoral debates extends to new distribution channels such as social media and on-demand streaming services. The research monitors the digital distribution channels of televised electoral debates during the 2023 elections in Spain, analyzing uncivil comments from the broadcasting accounts on Twitter (X). There is an uneven use of these new distribution channels among media groups, and a significant number of uncivil comments in X during televised events, although informative and neutral messages generate higher engagement.